Ta'sir Itqan al Tajwid 'ala Nata'ij al Ta'lim fi Ta'lim al Lughah al 'Arabiyyah fi al Fasl al Sabi' fi al Madrasah al Thaanawiyyah al Mawasir Lamasi Luwu - Naidin Syamsuddin; Mardi Takwim; Alkahfi (Al Ibrah: Journal of Arabic Language Education, 2023)
The effect of intonation proficiency on learning outcomes in Arabic language teaching in the seventh semester in high school Al-Mawasyer by Massey Lowu. This research aims to: (1) to know the mastery of intonation on students in the seventh semester in the secondary school pipes for Massey Luo (2) to know the learning results in teaching Arabic to students in the seventh semester in the secondary school pipes for Massey Luo (3) to know the effect of mastery of intonation on learning outcomes in teaching Arabic in the seventh semester in the secondary school pipes for Massey Luwu. The researcher uses seventh grade students in high school to become respondersand up to 15 people. Data collection techniques in which questionnaire and interview are the two main methods and are used by the researcher to find out the relationship between variable X and variable Y managed by the application SPSS 21. It uses other techniques such as observation and documentation of additional data. Success indicator In this research if the final result of the regression hypothesis test is rejected H0 and aH is accepted accordingly. And the results of the research: In this research, the effect between the X variable , which is the mastery of intonation regarding the letter exits, indicates the Y variable, which is the learning results of the Arabic language such as reading skill. The results are present from three tests: (1) Normal state test, (2) Variance homogeneity test, (3) Hypothesis test (regression test). The end result is successful and influenced by the conditions under which the rejection of H0 and the acceptance of aH with a significant level of 0.003 less than 0.05 with an impact rate of 51%.